Contamination of toxic metals and polycyclic aromatic hydrocarbons (PAHs) in rooftop vegetables and human health risks in Bangladesh. (2nd October 2021) - Tusher, Tanmoy Roy; Sarker, Md. Eusuf; Nasrin, Sumaya; Kormoker, Tapos; Proshad, Ram; Islam, Md. Saiful; Mamun, Shamim Al; Tareq, Abu Rayhan Mohammad
Abstract: Rooftop cultivation of vegetables is considered as a potential food source for urban population. However, rooftop products in the urban area can be contaminated by different types of pollutants like toxic metals and polycyclic aromatic hydrocarbons (PAHs). The present study is the first that investigated the concentrations of toxic metals and PAHs in rooftop soils and vegetables grown in the urban and peri-urban areas of Bangladesh. Red amaranth and Spinach were selected for rooftop cultivation, and both soil and vegetable samples were collected and analyzed for determining the concentrations of cadmium (Cd), copper (Cu), lead (Pb), and zinc (Zn) as toxic metals, while naphthalene, fluorene, phenanthrene, anthracene, pyrene, benzo(a)anthracene, and chrysene as PAHs. The study observed that urban rooftop soil and vegetables were highly contaminated with toxic metals and PAHs as compared to peri-urban rooftop samples. The metal concentrations were found in order of Zn > Cu > Pb > Cd, however, Pb and Cd concentrations in urban vegetables exceeded the safe limit. On contrary, negligible concentrations of PAHs were detected in both urban and peri-urban rooftop vegetables. The values of health risk indices revealed that the concentrations of toxic metals and PAHs in urban rooftop vegetables would not pose any carcinogenic and non-carcinogenic health risks for adults and children and thus are considered to be safe for consumption. The findings of this study will provide scientific evidence to the policy makers and public administrations for urban agriculture based policy formulation as well as will encourage the city dwellers towards urban rooftop agricultural practices.